If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -6x + 3x = 2 Combine like terms: -6x + 3x = -3x 8 + -3x = 2 Solving 8 + -3x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3x = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 2 + -8 -3x = 2 + -8 Combine like terms: 2 + -8 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 3w^2=-11w+6 | | 3.15*3.15=x | | 3y+6y+2x=90 | | 8=v+6 | | 6*(x+3)=3*(x+6) | | X-8.9=4.17 | | 3.147*3.147=x | | 100t+40=420 | | 6x-x=-55 | | 2x^2+3x+4=kx | | 3*(3x+2)=4x+1 | | 11=u-5 | | 3.14*3.14=x | | 24=-2(4v+6) | | -10(s+5)=-58 | | (3i)(3i^3)= | | 4*3.14=x | | 2*(x+1)+5=x | | 3r-8r=34 | | 165+5x=75+15x | | 34=8s-5s | | 4*(2x-5)=3*(3x+2) | | http://media.apexlearning.com/Images/200907/09/a2944e49-cb84-417a-9f9f-32fb31b69710.gif | | 2x(1)-y=5 | | 16-5r=-3(2r-8) | | 6X+8=-4x-2 | | -b^2-10b+36=0 | | 2x(0)-y=5 | | 5y+17=3x+7 | | 3.5-6x=x-1.75 | | 3.5-6=x-1.75 | | 44.5=-35.6+m |